Does canvassing increase voter turnout? A field experiment - Gerber, Alan S. (The National Academy of Sciences, 1999)
This paper reports the results of a randomized field experiment involving registered voters in the city of New Haven. Nonpartisan get-out-the-vote messages were delivered through personal canvassing shortly before the November 1998 election. We find that personal canvassing increased voter turnout by ≈6. The effect of personal contact seems to be slightly smaller for voters registered with a major political party and higher for unaffiliated voters, although the hypothesis that all voters are equally affected could not be rejected. Study of several alternative political messages provided equivocal evidence suggesting the superiority of a canvassing appeal that emphasizes the closeness of the election.